Pengembangan Perangkat Pembelajaran Kimia menggunakan Collaborative Learning untuk Melatih Keterampilan Berpikir Kreatif Siswa pada Materi Reaksi Redoks - Gani, Abdul (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The demands of 21st-century education emphasize the importance of mastering higher-order thinking skills, particularly creative thinking, which is crucial for problem-solving, generating new ideas, and adapting to change. However, conventional approaches in chemistry instruction, especially in redox reaction topics have yet to effectively foster the development of these skills. This study aims to develop a high school chemistry learning package based on a collaborative learning model to cultivate students’ creative thinking skills in redox reaction material. A Design-Based Research approach was employed in five stages: needs analysis, instructional design, initial implementation, revision and validation, and limited trial. Data were collected through validation sheets, observations, creative thinking skill tests, and student response questionnaires. The results indicate that the developed learning package demonstrates high validity and practicality and significantly enhances students’ creative thinking skills across four indicators: fluency, flexibility, originality, and elaboration. The implementation of the collaborative learning model fostered an interactive classroom environment, encouraged idea exchange, and deepened conceptual understanding. These findings suggest that the designed learning package is theoretically sound and effective for use in chemistry education. This study contributes to the innovation of instructional materials and recommends further exploration of digital media integration and long-term implementation.